Tingkat kemampuan teknik dasar passing atas pada ekstrakulikuler bola voli - Fajri, RIjal; Nasution, Nana Suryana; Sumarsono, Rhama Nurwansyah (Universitas Hamzanwadi, 2023)
The problem is that many students have difficulty performing the upper passing technique and the hand position is not correct and the hand is not straight when pushing the ball. The aim is to find out how much upper passing ability. This method is quantitative statistical in nature. The population was 40 students and sampling used probability sampling. The design uses a cross sectional survey. The instrument uses a 60-minute top passing test. Data collection techniques using measuring tests of passing ability levels. Data analysis techniques using descriptive kunatitatif percentages. The results were 50% and the frequency was 20, the overall data assessment process of 40 people who took the test, participants whose level of passing ability was included in the overall assessment. The low classification process is 40 people. The percentage is 80% according to the comparison between the results of the assessment procedure and the overall evaluation findings of the percentage of 32 and moderate categorization. The overall percentage comparison results show a percentage of 20 medium classification, while the overall results show a percentage of 32, 80% classification, and medium classification. The conclusion is that the overall assessment process is in the low category, with an average score in the high category. While the overall assessment results are in the medium category with a value in the low category.